A miniature scanning sun photometer for vertical profiles and mobile platforms. Issue 1 (2nd January 2016) - Murphy, D. M.; Telg, H.; Eck, T. F.; Rodriguez, J.; Stalin, S. E.; Bates, T. S.
ABSTRACT: A miniature sun photometer has been developed that makes continuous almucantar scans to measure solar irradiance and sky radiance in four wavelength bands set by interference filters. It has a well-defined field of view and can rapidly compensate for a tilting platform. It weighs less than 400 g and has an average power consumption of less than 5 W. Together, these characteristics make it suitable for vertical profiles using small balloons or unmanned aircraft systems (UASs). Preliminary results are presented showing measurements of optical depth and the phase function of scattered sunlight. An optical depth of about 0.03 in a clean boundary layer was measurable with an accuracy of better than 0.01. Copyright © 2016 American Association for Aerosol Research